When kidneys and lungs suffer together - Sorino, Claudio; Scichilone, Nicola; Pedone, Claudio; Negri, Stefano; Visca, Dina; Spanevello, Antonio (Journal of nephrology, 2019)
A significant interaction between kidneys and lungs has been shown in physiological and pathological conditions. The two organs can both be targets of the same systemic disease (eg., some vasculitides). Moreover, loss of normal function of either of them can induce direct and indirect dysregulation of the other one. Subjects suffering from COPD may have systemic inflammation, hypoxemia, endothelial dysfunction, increased sympathetic activation and increased aortic stiffness. As well as the exposure to nicotine, all the foresaid factors can induce a microvascular damage, albuminuria, and a worsening of renal function. Renal failure in COPD can be unrecognized since elderly and frail patients may have normal serum creatinine concentration. Lungs and kidneys participate in maintaining the acid-base balance. Compensatory role of the lungs rapidly expresses through an increase or reduction of ventilation. Renal compensation usually requires a few days as it is achieved through changes in bicarbonate reabsorption. Chronic kidney disease and end-stage renal diseases increase the risk of pneumonia. Vaccination against Streptococcus pneumonia and seasonal influenza is recommended for these patients. Vaccines against the last very virulent H1N1 influenza A strain are also available and effective. Acute lung injury and acute kidney injury are frequent complications in critical illnesses, associated with high morbidity and mortality. The concomitant failure of kidneys and lungs implies a multidisciplinary approach, both in terms of diagnostic processes and therapeutic management.